Bank integration and business volatility - Donald Morgan; Bertrand Rime; Philip Strahan (Federal Reserve Bank of New York, 2000)
We investigate how bank migration across state lines over the last quarter century has affected the size and covariance of business fluctuations within states. Starting with a two-state version of the unit banking model in Holmstrom and Triocole (1997), we conclude that the theoretical effect of integration on business cycle size is ambiguous, because some shocks are dampened by integration while others are amplified. Empirically, we find that integration diminishes employment growth fluctuations within states, and decreases the deviations in employment growth across states. In other words, business cycles within states become smaller with integration, but more alike. Our results for the United States bear on the financial convergence under way in Europe, where banks remain highly fragmented across nations.
Keywords: N1; G2; E3; 330; Bankensystem; Strukturwandel; Marktintegration; Fusion; Regionaler Konjunkturzyklus; Theorie; USA